PERAN MODAL SOSIAL SEBAGAI STRATEGI DALAM PENGEMBANGAN INDUTRI KERAJINAN TENUN DI DESA SUKARARA KABUPATEN LOMBOK TENGAH - Lalu Didik Apriawan; Siti Nurjannah; Oryza Pneumatica Inderasari (Journal of Urban Sociology, 2020)
The study was entitled "The Role of Social Capital as a Strategy in the Development of the Weaving Handicraft Industry in Sukarara Village". The development of the weaving industry has been started since the 1980s, but the process of developing the weaving industry is still relatively slow and has low competitiveness with handicraft industries is in Central Lombok. This study uses the theory and concept of social capital from Putnam. This study also uses a qualitative method with a case study approach. The main source in this study is the weaving craftsmen. The research location is Sukarara Village, Jonggat District, Central Lombok Regency. This research is a qualitative research which aims to explain and discover the role of social capital that is owned by the community in the development process of the weaving industry in the village of Sukarara. The focus of this research is identifying the role of social capital and knowing the obstacles in the development process of the weaving industry. This study aims to determine the role of social capital and its obstacles in the development process of the weaving industry in Sukarara Village.Keywords: Social Capital, Strategy, Weaving Crafts